Analysis of Gross Domestic Product determinants in the association of Southeast Asian Nations Region - Bima S; Anwar, Aminuddin (Jurnal Kebijakan Ekonomi dan Keuangan, 2024)
Purpose – This study aims to analyze gross domestic product (GDP) determinants in 7 ASEAN countries from 2010 – 2022.Methods – This study uses panel data analysis that selects random effects as the best model for analysis.Findings – This study concludes that investment, exports, and the Human Development Index (HDI) have a positive effect, and government expenditure positively affects gross domestic product (GDP). Meanwhile, imports have a negative effect on Gross Domestic Product (GDP).Implication – This study implies that there must be policies on investment, exports, and HDI through investment in education and health as well as trade cooperation agreements so that they have implications for improving the quality of the country's economy.Originality – This study contributes to analyze determinants of Gross Domestic Product (GDP), especially in ASEAN using a panel data approach. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis determinan produk domestic bruto (PDB) pada 7 Negara di ASEAN selama periode 2010 – 2022. Metode – Penelitian ini menggunakan analisis data panel yang secara spesifik memilih random effect sebagai model terbaik untuk analisis.Temuan – Penelitian ini menyimpulkan bahwa investasi, ekspor, Indeks Pembangunan Manusia (IPM) dan berpengaruh positif dan Pengeluaran Pemerintah berpengaruh positif terhadap Produk Domestik Bruto (PDB). Sementara itu, impor berpengaruh negatif terhadap Produk Domestik Bruto (PDB).Implikasi – Implikasi dari penelitian ini adalah harus adanya kebijakan terhadap investasi, ekspor, dan IPM melalui investasi pendidikan dan Kesehatan serta perjanjian kerjasama perdagangan sehingga berimplikasi terhadap peningkatan kualitas perekonomian negara.Orisinalitas – Penelitian ini berkontribusi terhadap analisis determinan Produk Domestik Bruto (PDB) khususnya di ASEAN menggunakan pendekatan data panel.